Prognostic significance of tumor-associated macrophages in solid tumor: a meta-analysis of the literature. - Qiong-wen Zhang; Lei Liu; Chang-yang Gong; Hua-shan Shi; Yun-hui Zeng; Xiao-ze Wang; Yu-wei Zhao; Yu-quan Wei (PLoS ONE, 2012)
PURPOSE: Tumor associated macrophages (TAMs) are considered with the capacity to have both negative and positive effects on tumor growth. The prognostic value of TAM for survival in patients with solid tumor remains controversial. EXPERIMENTAL DESIGN: We conducted a meta-analysis of 55 studies (n = 8,692 patients) that evaluated the correlation between TAM (detected by immunohistochemistry) and clinical staging, overall survival (OS) and disease free survival (DFS). The impact of M1 and M2 type TAM (n = 5) on survival was also examined. RESULTS: High density of TAM was significantly associated with late clinical staging in patients with breast cancer [risk ratio (RR)  = 1.20 (95% confidence interval (CI), 1.14-1.28)] and bladder cancer [RR = 3.30 (95%CI, 1.56-6.96)] and with early clinical staging in patients with ovarian cancer [RR = 0.52 (95%CI, 0.35-0.77)]. Negative effects of TAM on OS was shown in patients with gastric cancer [RR = 1.64 (95%CI, 1.24-2.16)], breast cancer [RR = 8.62 (95%CI, 3.10-23.95)], bladder cancer [RR = 5.00 (95%CI, 1.98-12.63)], ovarian cancer [RR = 2.55 (95%CI, 1.60-4.06)], oral cancer [RR = 2.03 (95%CI, 1.47-2.80)] and thyroid cancer [RR = 2.72 (95%CI, 1.26-5.86)],and positive effects was displayed in patients with colorectal cancer [RR = 0.64 (95%CI, 0.43-0.96)]. No significant effect was showed between TAM and DFS. There was also no significant effect of two phenotypes of TAM on survival. CONCLUSIONS: Although some modest bias cannot be excluded, high density of TAM seems to be associated with worse OS in patients with gastric cancer, urogenital cancer and head and neck cancer, with better OS in patients with colorectal cancer.